A case of peripheral ameloblastoma of retromolar trigone: Histopathological and immunohistochemical profile - Varun Surya; Priyanka Verma; Kavita Amale; Pooja Siwach (Wolters Kluwer Medknow Publications, 2015)
Peripheral ameloblastoma (PA) is a rare and unusual entity with histological characteristics similar to those of the common intraosseous ameloblastoma. In this paper, we present a case of PA in a 44-year-old male affecting the right retromolar trigone area along with its immunohistochemical profile using CK19 and Ber-EP4 markers.